Implementation of the Hadith “al-Bayyinatu 'ala al-Mudda'i wa al-Yamin 'ala Man Ankara” in the DSN MUI Fatwa on Guaranteeing Capital Returns - Prima Ariyo Widodo; Abdur Rohman; Yuliyanto Eko Prayitno; Alam Firman Syah (Demak Universal Journal of Islam and Sharia, 2024)
This study aims to analyze the implementation of the hadith "Al-Bayyinat 'ala Al-Mudda'i wa Al-Yamin 'ala Man Ankar" in the Fatwa of DSN MUI No: 105/DSN-MUI/X/2016 regarding the guarantee of capital return from the perspective of Maqashid Sharia. This hadith emphasizes the importance of evidence for the plaintiff and an oath for the repudiation, which is of great relevance in the context of financing and capital guarantee in the Sharia economy. Through a qualitative approach with a descriptive-analytical method, this study examines the application of the principles of the hadith in the DSN-MUI fatwa and assesses its conformity with the main objectives of sharia (maqashid sharia), namely safeguarding religion, soul, intellect, descendants, and property. The results of this research are expected to provide insight into the alignment between the implementation of fatwas and sharia principles, as well as guide practitioners in implementing contracts by sharia.